Avaliação Isocinética do Músculo Deltoide Após Artroplastia Invertida do Ombro - Bianca Sousa Barros (2020)
Background: Reverse Shoulder Arthroplasty depends on the Deltoid muscle to improve function and stability of the shoulder. Deltoid tension and pre- and postoperative conditions are key factors. Although good subjective results are reported, functional outcomes have shown variable improvements. The purpose of this study is to understand the biomechanical and functional influence of the Reverse Shoulder Arthroplasty. Methods: Fifteen participants after unilateral Reverse Shoulder Arthroplasty, were evaluated with isokinetic dynamometer (Abduction/Adduction and Forward Flexion/Extension), Electromyography and Constant-Murley Score. The arm without the prosthesis was considered the best performance status and used as comparison. Arm-length was measured and calculated the difference between arms. Participants were divided in two groups according to Constant-Murley Score of the arm without prosthesis: Group 0 (superior/equal to 80) and Group 1 (inferior to 80). Findings: Significant differences in isokinetic parameters were observed, especially in Group 0, with the arm without prosthesis having better results. The Electromyography showed that Group 0 has an overall decrease of the electromyography activity in the arm with prosthesis, especially in the anterior and middle portion of the Deltoid, in Abduction and Forward Flexion. Group 1 revealed less significant differences. Interpretation: Isokinetic evaluation combined with Electromyography is a useful tool to assess muscular and joint outcomes. This study demonstrated that Reverse Shoulder Arthroplasty has a significant effect in range of motion and strength of the shoulder joint and the Deltoid. Shoulders with the prosthesis presented worse performance, but these changes may only be significant when a higher functional level is present.